KONSEP MODERASI BERAGAMA: Perspektif Husein Ja'far Al Hadar dan Urgensinya pada Pendidikan Agama Islam - Fadilah, Annisa Nur (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
The Concept of Religious Moderation in the Perspective of Husein Ja'far Al Hadar and Its Relevance to Islamic Religious Education and the 1945 Constitution (The Study of God's Book Library in Your Heart) No exception to the conception of religious moderation in the book There is God in Your Heart by Habib Husein Ja'far Al Haddar this is a hot topic of discussion. From his perspective book, we can then draw a clear conclusion, namely that Islamic teachings are not only approached through literal understanding but also require horizontal practice, namely joint practice with other humans. Habib Husein in his book describes the phenomena that are currently happening in a practical way but still sourced from classic books, namely the Al-Quran and hadith. This research uses the library study method. The results of this study, the concepts presented related to diverse moderation are closely related to Islamic Religious Education and the 1945 Constitution. Abstrak Konsep Moderasi Beragama Perspektif Husein Ja’far Al Hadar dan Relevansinya Pada Pendidikan Agama Islam dan UUD 1945(Studi Pustaka Buku Tuhan ada Di Hatimu) Tak terkecuali dengan konsepsi moderasi beragama yang ada pada buku ada Tuhan di Hatimu karya Habib Husein Ja’far Al Haddar ini menjadi sebuah perbincangan yang hangat. Dari buku perspektif beliau ini kita dapat kemudian ditarik benarnag merah yakni ajaran Islam itu tidak hanya didekati melalui pemahaman yang leterlek namun juga memerlukan praktik secara horisoantal yakni praktik bersama dengan manusia yang lain. Habib Husein dalam bukunya tersebut menjabarkan fenomena yang sedang terjadi saat ini dengan praktis namun tetap bersumber kepada kitab klasik yakni Al-Quran dan hadits. Penelitian ini menggunakan metode studi Pustaka. Hasil dari penelitian ini kosnep yang disajikan terkait moderasi beramagam berkaitan erat dengan Pendidikan Agama Islam dan konstitusi UUD 1945